ChemInform Abstract: La(OTf)3‐Catalyzed, Three‐Component Synthesis of Spiro[Indolo‐3, 10′‐indeno[1, 2‐b]quinolin]‐2, 4, 11′‐triones in PEG‐400 under Conventional Heating and Ultrasonic Irradiation. Issue 31 (14th July 2016) - Kumari, Sudesh; Rajeswari, M.; Khurana, J. M.
Abstract: An efficient and environmentally benign approach for the synthesis of the title triones by one‐pot, three‐component condensation of indandione, isatins, and enaminones is developed.